Staging Bali: The Transformation of Cultural Performance Through Disneyfication and Spectacle - Bestari, Ni Made Prasiwi; Srikandi, Melati Budi; Shantika, Budi (Gondang: Jurnal Seni dan Budaya, 2025)
This study explores the transformation of Balinese and Indonesian cultural performances through the processes of Disneyfication and spectacle, focusing on three popular case studies: the Kecak dance at Uluwatu Temple, the Devdan Show in Nusa Dua, and the Varuna Show at Bali Safari. Through comparative analysis and the integration of audience reviews, this research examines how traditional rituals are increasingly repackaged as theatrical entertainment designed to appeal to global tourists. The findings reveal a progressive shift from sacred, community-centered expressions to visually driven, commercially oriented performances. While these adaptations enhance the accessibility and visibility of Indonesian culture, they also raise critical questions about authenticity, commodification, and the loss of spiritual depth. The study argues that cultural performances are not only shaped by tradition but are continually reimagined through the dynamics of tourism, technology, and global consumer expectations. This evolution invites reflection on the broader implications of cultural tourism in shaping how heritage is presented, perceived, and preserved in contemporary society.